PERBEDAAN INTENSITAS NYERI PUNGGUNG BAWAH IBU HAMIL TRIMESTER III YANG DIBERIKAN GYM BALL - Anggraeni, Putu Eka Putri; Armini, Ni Wayan; Tedjasulaksana, Regina (Fakultas Ilmu Kesehatan, 2025)
Pain management in maternity care can use various methods, namely pharmacological and non-pharmacological. Counterpressure massage techniques can activate endhorphin compounds so that the transmission of pain messages can be inhibited, which can lead to a decrease in pain intensity. Aromatherapy molecules stimulate the limbic system which can reduce anxiety that leads to pain because there is a direct relationship between pain and anxiety. The aim of this study was to determine the difference in pain intensity in mothers during the first active phase of labor before and after being given a combination of counterpressure massage with lavender aromatherapy. This research design was a pre-experimental one group pre-test and post-test design approach carried out at the Wangaya Denpasar Regional Hospital in March-April 2024. The sample size was 35 people, data was collected using the Wong-Baker Faces Pain Rating Scale observation sheet. The normality test used was the Shapiro-Wilk test because the data was not normally distributed, then the next hypothesis test was carried out by the wilcoxon test with a sig (2-tailed) value = 0.000 < 0.05, so the hypothesis could be accepted, which means there is a difference in the intensity of pain in mothers giving birth. stage I active phase. The conclusion is that combination counterpressure massage therapy with lavender aromatherapy can reduce pain intensity. Midwives can use non-pharmacological methods to reduce the pain level of mothers in labor, such as counterpressure massage with lavender aromatherapy